2017
DOI: 10.1002/ijc.30598
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the incidence of cancer in Norway

Abstract: Article category: Research ArticleNovelty and Impact: Traditionally there have been large differences in cancer incidence across geographic regions, and even though this picture is changing with changes in lifestylerelated cancers in low-income countries, geographic differences still exist. We have compared cancer incidence in immigrant groups with that in individuals born in Norway, and have found surprisingly large differences for some cancers. The Norwegian setting is well suited for these studies because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
32
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 37 publications
7
32
1
5
Order By: Relevance
“…6 A previous study, investigating cancer stage distribution in immigrants compared to the Norwegian host population, showed that non-Western women had higher risk of being diagnosed with a more advanced stage of breast cancer. 6 A previous study, investigating cancer stage distribution in immigrants compared to the Norwegian host population, showed that non-Western women had higher risk of being diagnosed with a more advanced stage of breast cancer.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…6 A previous study, investigating cancer stage distribution in immigrants compared to the Norwegian host population, showed that non-Western women had higher risk of being diagnosed with a more advanced stage of breast cancer. 6 A previous study, investigating cancer stage distribution in immigrants compared to the Norwegian host population, showed that non-Western women had higher risk of being diagnosed with a more advanced stage of breast cancer.…”
mentioning
confidence: 98%
“…Historically, immigrants in Norway have had lower incidence of lifestyle-related cancers and higher incidence of certain cancers caused by infections than the host population. 6 A previous study, investigating cancer stage distribution in immigrants compared to the Norwegian host population, showed that non-Western women had higher risk of being diagnosed with a more advanced stage of breast cancer. 7 Non-Western immigrants have also been shown to have lower attendance rate to both cervical and mammography screening.…”
mentioning
confidence: 98%
“…I de siste tiårene har også andelen av innvandrere økt, fra 2,5 % i 1984 til naer 14 % i 2017 (1). Vi har nylig vist at innvandrere har lavere forekomst av alle kreftformer samlet, men samtidig høyere risiko for leverkreft hos begge kjønn og lungekreft hos menn (2). Vi har altså etter hvert fått en økende andel av befolkningen som har ulik risiko for kreft, og det er derfor interessant å se på om dette har påvirket de nasjonale kreftratene som publiseres årlig av Kreftregisteret i Cancer in Norway (3).…”
Section: Fortolkningunclassified
“…Et eksempel er leverkreft. Her har vi sett en økning i forekomsten, og innvandring har vaert fremsatt som en forklaring på denne økningen (3), siden flere innvandrergrupper har økt forekomst (2).…”
Section: Fortolkningunclassified
“…Sufficient responsiveness and interpretability outcomes are presented in bold.of the cancer population, as the incidence of cancer is lower among non-European immigrants compared to native European people in general. Especially for colorectal, breast and gynaecological cancer(Hjerkind et al, 2017), which was the main cancer population of our study. The second number is not representative of the general Dutch working population nor representative of the cancer population as the prevalence of cancer among female working population is only slightly higher compared to males and as more males than females have paid work (Netherlands Cancer Registery; Statistics Netherlands).…”
mentioning
confidence: 89%